2018
DOI: 10.1038/s41598-018-24263-9
|View full text |Cite
|
Sign up to set email alerts
|

The LetA/S two-component system regulates transcriptomic changes that are essential for the culturability of Legionella pneumophila in water

Abstract: Surviving the nutrient-poor aquatic environment for extended periods of time is important for the transmission of various water-borne pathogens, including Legionella pneumophila (Lp). Previous work concluded that the stringent response and the sigma factor RpoS are essential for the survival of Lp in water. In the present study, we investigated the role of the LetA/S two-component signal transduction system in the successful survival of Lp in water. In addition to cell size reduction in the post-exponential ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 98 publications
(165 reference statements)
2
17
0
Order By: Relevance
“…The N-terminus of P. salmonis LetS contains two conserved signal sensing domains: DUF2222 (residues 36-168) and HAMP (residues 191-243), and two transmembrane domains located between residues 10 to 32 and residues 165 to 187. C-terminal to these domains are found the transmitter, receiver, and histidine phosphotransfer domains, which is a characteristic structure of tripartite sensor kinases (Mendis et al, 2018). In L. pneumophila, LetS acts by shutting down a number of genes related to growth when the bacterium is exposed to water, improving its culturability and survival in a low-nutrient environment (Mendis et al, 2018).…”
Section: Expression Patterns Of Key Stringent Response Genes Of P Samentioning
confidence: 99%
“…The N-terminus of P. salmonis LetS contains two conserved signal sensing domains: DUF2222 (residues 36-168) and HAMP (residues 191-243), and two transmembrane domains located between residues 10 to 32 and residues 165 to 187. C-terminal to these domains are found the transmitter, receiver, and histidine phosphotransfer domains, which is a characteristic structure of tripartite sensor kinases (Mendis et al, 2018). In L. pneumophila, LetS acts by shutting down a number of genes related to growth when the bacterium is exposed to water, improving its culturability and survival in a low-nutrient environment (Mendis et al, 2018).…”
Section: Expression Patterns Of Key Stringent Response Genes Of P Samentioning
confidence: 99%
“…In order to survive against harsh environmental conditions, legionella enters a "reversible dormant state", known as the viable but not culturable state (VBNCS) [24] When environmental conditions improve, like in the case of phagocytosis by Acanthamoeba castellanii, the bacterium represses its virulent traits and goes into its exponential phase, in which it replicates within the protozoa [6]. This process of replication takes round 15 hours to complete [25]. Once lack of nutrients and environmental stress strikes, L. pneumophila coordinates its differentiation to the mature intracellular form (MIF) and the stationary phase form (SPFs), both with virulent traits characterized by high motility and cytotoxicity and proceeds to lyse the cell and infect cells in proximity.…”
Section: Strategymentioning
confidence: 99%
“…Once lack of nutrients and environmental stress strikes, L. pneumophila coordinates its differentiation to the mature intracellular form (MIF) and the stationary phase form (SPFs), both with virulent traits characterized by high motility and cytotoxicity and proceeds to lyse the cell and infect cells in proximity. Although studies are lacking on the mechanisms by which the host cell is lysed by the bacterium [24,25]. SPFs present flagella, loose outer membrane, and a well-defined inner membrane, while MIFs typically appear as stubby rods with complex envelope, both being able to colonize alveolar macrophages [24].…”
Section: Strategymentioning
confidence: 99%
“…This response results in the production of chaperones and proteases to refold or destroy misfolded proteins and aggregates (14). In Lp, the two-component system LetA/S is the only regulatory system known to be important for surviving thermal stress (15).…”
Section: Introductionmentioning
confidence: 99%
“…A transcriptomic analysis of a letS mutant in water revealed that tsp is downregulated in the mutant (15). In addition, the expression of tsp was downregulated in a cpxR mutant grown to PE phase, suggesting CpxR is also required for expression of tsp in PE phase (41).…”
Section: Introductionmentioning
confidence: 99%